Advances in Lithium–Oxygen Batteries Based on Lithium Hydroxide Formation and Decomposition - Zhang, Xiahui; Dong, Panpan; Song, Min-Kyu (Frontiers in Chemistry, 2022)
The rechargeable lithium–oxygen (Li–O2) batteries have been considered as one of the promising energy storage systems owing to their high theoretical energy density. As an alternative to Li–O2 batteries based on lithium peroxide (Li2O2) cathode, cycling Li–O2 batteries via the formation and decomposition of lithium hydroxide (LiOH) has demonstrated great potential towards the development of practical Li–O2 batteries. However, the reversibility of LiOH-based cathode chemistry remains unclear at the fundamental level. Here, we review the recent advances made in Li–O2 batteries based on LiOH formation and decomposition, focusing on the reaction mechanisms occurring at the cathode, as well as stability of Li anode and cathode binder. We also provide our perspectives on future research directions for high-performance, reversible Li–O2 batteries.